The Role of Human Capital Investment In Economic Growth: Evidence From Cross-Country And Regional Studies - Hutabarat, Indra Setiawan; Hutabarat, Sinta Veronika; Siregar, Mira Yosefa; Zelani, Danu Irwan; Suganda, Hikmah Anum (Institute of Computer Science (IOCS), 2026)
This study analyzes the effect of human capital investment on economic growth using a quantitative econometric approach based on panel data analysis. Economic growth is a crucial indicator of development, reflecting a country’s ability to improve welfare and productivity. In recent years, human capital—represented by education level and labor quality—has gained increasing attention as a key driver of sustainable economic growth. This research aims to examine the contribution of human capital to economic growth while controlling for physical capital formation, labor force participation, and income inequality.The study employs secondary data collected from official statistical sources covering several regions over a specific period. Panel data regression techniques are applied to capture both cross-sectional and time-series variations. The estimation includes Pooled Ordinary Least Squares, Fixed Effects Model, and Random Effects Model, with model selection determined through Chow and Hausman tests. Classical assumption tests are conducted to ensure the validity and robustness of the model.The empirical results indicate that human capital investment has a positive and statistically significant impact on economic growth. Regions with higher levels of education and labor quality tend to experience faster economic growth. Conversely, income inequality shows a negative relationship with economic growth, suggesting that unequal access to human capital may hinder long-term development. These findings emphasize the importance of inclusive human capital policies to support sustainable and equitable economic growth.